Greenhouse gas (GHG) emissions derived from two types of fertilization of pineapple crops (Ananas comosus) in ultisols from Sarapiquí, Costa Rica, taking the secondary forest as reference - Coto Brenes, Sofía (2021)
Pineapple production in Costa Rica increased significantly in the last years, impacting agrochemical usage, which cause greenhouse gas emissions, as well as physical, chemical, and biological changes in the soil. This project evaluates the GHG emissions generated by two different types of fertilization of pineapple crops in ultisol soils in Sarapiqui, Costa Rica. Samples were collected in three different locations delimited by two 20 x 40 m plots, which were also subdivided into two 20 x 20 m subplots. Gas samples were collected using two techniques: static chamber and continuous gas analyzer (LGR), during both dry and rainy seasons in 2018-2019. The measured CO2 fluxes registered a positive correlation with organic matter content and carbon concentration in the soil, which varied slightly between seasons. N2O fluxes also varied between seasons, with organic management registering higher data (11 to 161 mgm-2d-1) in the rainy season and the forest in the dry season (3 to 76 mgm-2d-1). Conventional fertilization was characterized by soils with less organic matter, carbon, and moisture, which reduces the microbial activity, a situation that produces higher GHG emissions.